If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15p = 7(p + -9) Reorder the terms: 15p = 7(-9 + p) 15p = (-9 * 7 + p * 7) 15p = (-63 + 7p) Solving 15p = -63 + 7p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7p' to each side of the equation. 15p + -7p = -63 + 7p + -7p Combine like terms: 15p + -7p = 8p 8p = -63 + 7p + -7p Combine like terms: 7p + -7p = 0 8p = -63 + 0 8p = -63 Divide each side by '8'. p = -7.875 Simplifying p = -7.875
| k^2+14k+13=0 | | -2(1+4n)=34+n | | a^2-4a=16+2a | | 20+4x=44r | | 14+23=x | | 2(x-2)=3(1+x) | | 17-w=8 | | 0.6(t+18)=-3(2-t) | | y-4.1=2.75 | | y=2.9+0.4x | | 57-(-3x+4)=5(x+7)+x | | 2x^3+x^2+4x-15=y | | 0.5+d=-3.2 | | 2(4x-3)=8x+2 | | 3x^2+3x=-5 | | -4+7a=-4-4(1-2a) | | 3x+y+3=26 | | x^3-13xL^2+30x=0 | | 6-3t=8t-14 | | 0.5+d=-31/5 | | 1.4z+8=12 | | 1132=16+19t+167t | | f(x)=x^4-5x^2+2 | | x=2f-3b*a | | 4(5)-2y=14 | | 10-4y=-5 | | 2x(x+5)-3(x^2+2x-1)=9-5x-x^2 | | -4+7a=-4-(1-2a) | | 4(3X-1)-8X=-8 | | -6+5=x-23 | | 7y-4=3x+16 | | -10x-42=128 |